Isolation drives species gains and losses of insect metacommunities over time in a mountaintop forest archipelago - da Silva, Pedro Giovâni; Beirão, Marina do Vale; de Castro, Flávio Siqueira; Perillo, Lucas Neves; Camarota, Flávio; Solar, Ricardo R. C.; Fernandes, Geraldo Wilson; Neves, Frederico de Siqueira (Journal of biogeography, 2023)
AimWe evaluated the effects of forest island size, isolation and area in the landscape driving temporal changes of insect biodiversity in a mountaintop forest archipelago. We expected that (i) in smaller, less isolated forest islands, changes in insect composition are more prominent, primarily driven by gains over time; (ii) more forest in the landscape leads to increased gains of vagile species over time, regardless of forest island size and isolation; (iii) less vagile groups undergo heterogenisation, while highly vagile groups experience homogenisation due to differing dispersal capabilities.LocationEspinhaço Range Biosphere Reserve, Brazil.TaxonInsects.MethodsWe used ants, dung beetles, bees, wasps and butterflies as study models to represent a gradient of low‐to‐high dispersal capability. We evaluated the colonisation‐ and extirpation‐resultant components of temporal β‐diversity using area‐ and isolation‐related variables as predictors.ResultsDistinct colonisation‐ and extirpation‐resultant homogenisation and heterogenisation processes are acting according to each insect group, likely due to different dispersal capabilities. Species losses dominated in ants, with widespread and rare species being lost. Butterflies gained species, represented mainly by widespread species, leading to an increased colonisation‐resultant homogenisation. Distance to neighbouring forest islands was the underlying predictor affecting the temporal β‐diversity of insect groups, and also species gains and losses but differently according to the survey period. Effects of the forest amount in the landscape increased the temporal β‐diversity of bees and butterflies but decreased that of ants, dung beetles and wasps.Main ConclusionsThese findings provide valuable biogeographic insights into the complex interactions between forest island characteristics, landscape attributes, and dispersal capabilities that shape the temporal dynamics of insect biodiversity on mountaintops. Conserving the forest amount in the landscape and keeping forest connectivity among forest islands are necessary because the temporal dynamics of local colonisation and extirpation can depend on the organisms' dispersal capability.